The effect of regular aerobic exercise on urinary brain-derived neurotrophic factor in children - Yunita Fediani; Masayu Rita Dewi; Muhammad Irfannuddin; Masagus Irsan Saleh; Safri Dhaini (Indonesian Pediatric Society, 2014)
Background Nervous system development in early lifeinfluences the quality of cognitive ability during adulthood.Neuronal development and neurogenesis are highly influencedby neurotrophins. The most active neurotrophin is brain-derivedneurotrophic factor (BDNF). Physical activity has a positiveeffect on cognitive function. However, few experimental studieshave been done on children to assess the effect of aerobic regularexercise on BDNF levels.Objective To assess the effect of regular aerobic exercise onurinary BDNF levels in children.Methods This clinical study was performed in 67 children aged6-8 years in Palembang. The intervention group (n=34) engagedin aerobic gymnastics three times per week for 8 weeks, while thecontrol group (n=33) engaged in gymnastic only once per week.Measurements of urinary BDNF were performed on both groupsbefore and after intervention. Mann-Whitney and Wilcoxon ranktests were used to analyze the differences between groups.Results There was no difference in urinary BDNF levels betweenthe two groups prior to the intervention. After intervention,the mean urinary BDNF levels were significantly higher in theintervention group than in the control group, 230.2 (SD 264.4)pg/mL vs. 88.0 (SD 35.4) pg/mL, respectively (P=0.027). We alsofound that engaging in aerobic gymnastics significantly increasedurinary BDNF levels from baseline in both groups (P=0.001).Conclusion Regular aerobic exercise can increase urinary BDNFlevels and potentially improve cognitive function. Aerobic exerciseshould be a routine activity in school curriculums in combinationwith the learning process to improve children’s cognitive ability.